Kebijakan Ekonomi Islam untuk Mengurangi Konsentrasi Kepemilikan dan Ketimpangan Distribusi - Kholidin Muslim; Ahmad Mifdlol Muthohar (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Inequality in wealth distribution and the concentration of asset ownership are major challenges in modern economic development that can lead to social disparities. This study aims to analyze Islamic economic policies in reducing ownership concentration and wealth distribution inequality in order to achieve sustainable economic justice. The research employs a descriptive qualitative approach through a literature review, analyzing secondary data from Islamic economics literature and scientific articles using a narrative method. The findings indicate that Islamic economics places human welfare at the center of its objectives through the realization of falah (well-being) and maslahah (public benefit), which are aligned with the principles of Maqashid al-Shariah. Efforts to reduce ownership concentration and wealth inequality are implemented through redistributive instruments such as zakat, infaq, sadaqah, waqf, and the Islamic inheritance system (faraidh), as well as through the prohibition of exploitative practices such as riba (usury/interest) and monopoly (ihtikar). These policies are consistent with Indonesian legal frameworks, including Article 33 of the 1945 Constitution and Law No. 5 of 1999. Future strengthening strategies require economic and financial reconstruction through the development of the real sector, empowerment of micro, small, and medium enterprises (MSMEs), the elimination of interest-based systems, and the optimization of Islamic social finance governance to create inclusive and equitable economic opportunities for all segments of society.